Zasada dobra wspólnego a demokracja. Próba analizy stanowiska J. Maritaina - Turek, Joanna (Annales. Etyka w Życiu Gospodarczym, 2008)
In the following paper the author presents and analyses J. Maritain’s social theory. The FrenchThomist attempted to associate the principle of common good (that plays the main role in the Christiansocial thought) with democracy. Maritain claims that only democracy can be regarded as an acceptableform of government, i.e. the one that satisfies rational and moral requirements (which, according tothe Thomists, are the same). Such a statement put forward by the Thomist philosopher emphasisesthe necessity of asking a number of questions of the human nature, human dignity and humanautonomy; it also demonstrate how to introduce the ethical values into the realm of democratic politics,which in its turn is described as axiologically neutral by contemporary political theories. J. Maritain’sviews on those issues were taken into consideration by Catholic intellectuals and were announcedbefore the Second Vatican Council. Regarding the time they were widely opened to the contemporaryideas. Consequently, they contributed to the significant development of the current attitudeof the Catholic Church to the present political and social problems.